## CrazyC246 3 years ago How do I solve 4(2x + 1)- 3 = -3(x - 4)?

1. Romero

You have to distribute out what's outside the parentheses first. Do you know how to do that?

2. CrazyC246

No

3. Calcmathlete

Distributive Preoperty: \(a(b + c) = ab + ac\)

4. CrazyC246

Oh wait yes.

5. Romero

That's basically means that the number outside of the parentheses you have to multiply it to everything inside the parentheses

6. CrazyC246

I got 8x+4-3=-3x+12+12, is it right?

7. Romero

8x+4-3=-3x+12 You added an extra 12 on the right hand side

8. Romero

But other than that you are right. Think you can handle it from there?

9. CrazyC246

Oh oops, lol.

10. CrazyC246

Now what do I do?

11. Romero

You want all the x's to be on one side and all the numbers on the other side. Let's start by adding 3x to both sides. This will get rid of the -3x from the right hand side. 8x+4-3=-3x+12 8x+3x+4-3=-3x+3x+12 8x+3x+4-3=12 11x+4-3=12

12. Romero

From there you can simplify it even further by doing this 4-3?

13. CrazyC246

Would the answer be 1, right?

14. Romero

Yeah you are right man Good job!

15. CrazyC246

|dw:1342743342637:dw|

16. CrazyC246

Thank you =)